Nurturing global consciousness through internationalization - Helleve, Mette Birgitte (Nordic Journal of Comparative and International Education (NJCIE), 2019)
The topic of this article is nurturing global consciousness through internationalization in teacher education. As a teacher educator, I have been supervising 29 student teachers in their three-month practice in Namibia and Uganda over a four-year period. Here I have focused on the students' experience according to global consciousness with a primary focus towards their global sensitivity. The purpose of this article is threefold. First I describe the nuances of global consciousness and the connection between the three sub-areas: global sensitivity, global understanding, and global self-representation. The two concepts intersubjectivity and attunement will provide a meaningful contribution to the definition of global consciousness. Secondly, I argue that internationalization, as a three-month-long practice abroad in itself, is not sufficient to nurture global consciousness. Thirdly, I describe a pedagogical approach to nurture teacher students’ global consciousness through a set of five different tasks. The research question for this article is: How can initial teacher education contribute to nurturing student teachers’ global consciousness through mentoring and practice abroad? Methodologically the study is grounded in a phenomenological tradition. In the analysis of the material, I have focused on the students' experiences concentrated toward the concept of global consciousness and the sub-areas mentioned above.